Caribbean Report 30-04-1990 - Crosskill, Hugh (anchor); Brathwaite, Nicholas (interviewee); Stainer, Robin (analyst); Baptiste, Sandra (correspondent); Mckenzie, L. (interviewee); Dark, Ian (correspondent); Benn, Nigel (interviewee) (The British Broadcasting Corporation, 1990)
The World Union of Guyanese for Democracy protests in support of the exile community of Guyanese concentrated in New York, London and Toronto. In St. George’s, Grenada a major fire destroys the financial complex of the government, including the buildings of the Treasury, Inland Revenue, the Post Office and the Government Printery. With damages estimated between fifteen and seventeen million dollars, Prime Minister Nicholas Brathwaite is seeking assistance in determining the cause of the fire and rules out the possibility of arson. Following the Financial News, sugar prices on the world market hits a nine-year high and ACP members will be meeting in London on May 9th to discuss measures aimed at safe guarding the sugar industry in the light of changing economic and political situations in Europe. The next segment covers the conclusion of a three-day conference on Natural and Alternative Medicine in Havana, Cuba attended by medical practitioners from over one hundred countries. Cuba is exploring ways to reduce the country’s existing health cost by returning to alternative medicine. The final segment focuses on the injuries of British Middleweight boxer, Nigel Benn, after his victory against American Doug Dewitt in the World Boxing Organization Title fight.
1. Hugh Crosskill interviews Mike Persaud of the World Union of Guyanese for Democracy (00:00-02:11)
2. Major fire in St. Geroge's, Grenada destroys the government's financial complex (02:12-04:40)
3. Financial News (04:41-06:21)
4. Rise in sugar prices in the world market may not translate into profits for Caribbean exporters to Europe under the Lome Convention. Sandra Baptiste reports from London with an interview with L. McKenzie, a senior trade official in the Development Division of the European Commission (06:22-08:39)
Keywords: Democracy -- Guyana; Exiles -- Guyana -- New York (State) -- New York; Exiles -- Guyana -- London; Exiles -- Guyana -- Toronto; Fire -- Saint George's (Grenada); Sugar trade -- Prices; Alternative medicine -- Cuba -- Congresses; Medical care -- Cuba; Boxers (Sports) -- England; Boxing matches; World Union of Guyanese for Democracy; World Boxing Organization